Inflationary Regime of the Evolution of the Scale Factor in the Relativistic Theory of Gravitation with a Graviton Mass; Russian Physics Journal; Vol. 61, iss. 1 - Lasukov V. V. Vladimir Vasilievich (2018, 2018)
Title screen